IMPACT OF EDUCATIONAL INTERVENTION ON KNOWLEDGE, ATTITUDE, AND PRACTICES OF URBAN COMMUNITY PHARMACISTS TOWARD ADVERSE DRUG REACTION REPORTING IN A SOUTH INDIAN CITY - Ms, Srikanth; ADEPU, RAMESH; S, Nagaraj (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To assess the knowledge, attitude, and practices (KAP) of community pharmacists toward adverse drug reaction (ADR) reporting and also to evaluate the impact of the educational program on community pharmacist's knowledge and perception toward ADR reporting. Methods: A prospective cross-sectional study was carried out by administering a validated questionnaire before and after the educational program on a sample of 26 community pharmacists. The baseline score of pre-training KAP was compared with the post-training KAP. The SPSS statistical version 19 was used to compare the difference in the KAP of the pharmacists before and after the educational program. Frequencies and percentage were used to measure demographic details of the participants. Results: 26 community pharmacists have participated in the study. The mean pre-training KAP score was increased from 4.30±2.02 to mean posttraining score of 7.32±0.94. After the educational program, 92.30% (n=24) of participants were able to identify potential risk factors responsible to cause ADRs, and 80.76% (n=21) of participants were aware of the consequence of ADRs. Upon educational intervention 73.07% (n=19) of participants disagree with the statement of ADR reporting in the community pharmacies lead to additional workload and were confident about their knowledge in ADR reporting and monitoring. Conclusion: The study concludes that the educational intervention has increased the KAP of the trained community pharmacists toward ADR reporting. Keywords: Community pharmacists, Adverse drug reaction reporting, Educational intervention, Knowledge, Attitude and practices.